2021
DOI: 10.3390/nu13124434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Tea Consumption on Urinary Risk Factors for Kidney Stone Formation

Abstract: Copious fluid intake is the most essential nutritional measure in the treatment of urolithiasis, and is suggested to be a protective factor in the primary prevention of urinary stone formation. Although the intake of black tea contributes to daily fluid intake, the high oxalate content could outweigh the beneficial effect of urine dilution. The present study investigated the effect of black tea consumption on urinary risk factors for kidney stone formation. Ten healthy men received a standardized diet for a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The expressions of SLC26 family members and their physiologic roles vary considerably between species, suggesting different pathogenic mechanisms of SLC26 mutants between humans and animal models ( SOLEIMANI, 2013 ). Abnormalities of urinary ion concentrations, such as hyperoxaluria, are important pathogenic factors ( SIENER and Hesse, 2021 ). The SLC26 family is centrally involved in oxalate and sulfate ion transport in urolithogenesis, and the STAS structural domain is an important site of action.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of SLC26 family members and their physiologic roles vary considerably between species, suggesting different pathogenic mechanisms of SLC26 mutants between humans and animal models ( SOLEIMANI, 2013 ). Abnormalities of urinary ion concentrations, such as hyperoxaluria, are important pathogenic factors ( SIENER and Hesse, 2021 ). The SLC26 family is centrally involved in oxalate and sulfate ion transport in urolithogenesis, and the STAS structural domain is an important site of action.…”
Section: Discussionmentioning
confidence: 99%
“…However, Shu et al and Wang et al reported that tea consumption was associated with a lower risk of urolithiasis [ 40 , 41 ], especially green tea, which was indicated to have a protective function in kidney stone formation [ 8 ]. While black tea intake did not correlate with a decreased incidence of kidney stones, it did not elevate the risk either [ 42 ]. Our study lends further support to these findings by identifying tea consumption as a causal factor associated with a lower risk of kidney stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from a cohort study suggested only a modest positive association between dietary oxalate intake and the risk of kidney stone formation ( 37 ). Besides, the consumption of the oxalate-rich black tea did not significantly alter 24-h urinary oxalate excretion ( 38 ). The modest effects of urinary oxalate might have been offset by a large increase in fluid intake while drinking tea.…”
Section: Discussionmentioning
confidence: 99%